Storage stability and quality characteristics of fried fish crackers added with rice bran flour and resistant starch - Idris, 'Atiqah 'Aqilah (2018)
Fried fish crackers are very popular traditional snack food in Malaysia and many Southeast Asian countries. However, the main concern is on the deteriorating in fried cracker due to the lipid oxidation, and lipid co-oxidation on the fish protein. The shelf life stability of fried fish cracker is usually less than three months due to lipid oxidation reaction which will result in rancidity, alteration of textural properties and overall degradation of the product quality. Therefore, the aim of the present work was to measure the storage stability and quality characteristics of fried fish crackers added with rice bran flour and resistant starch as influenced by storage temperature. Fried fish crackers, fish crackers added with 6% (w/w) rice bran flour and fish crackers added with 16.7% (w/w) resistant starch were prepared. The physicochemical properties, lipid stability and protein characteristics were examined at 25, 40 and 60°C for three months. Fried fish crackers were packed into two types of packaging with four different layers of; (i) polyethylene terephthalate-polyethylene-aluminium-linear low density polyethylene (PET-PE-ALU-LLDPE) with 0.5 moisture vapor transmission rate (MVTR) and 0.5 oxygen transmission rate (OTR), and (ii) oriented polypropylenepolyethylene- metallized polyethylene terephthalate-linear low density polyethylene (OPP-PE-MPET-LLDPE) with 0.08 MVTR and 0.08 OTR. The linear expansion and oil absorption in fried fish cracker was 75.67 ± 5.86% and 27.86 ± 0.79%, respectively. The linear expansion and oil absorption of the fried fish cracker with rice bran and resistant starch was 53.33 ± 2.08%; 18.56 ± 0.39% and 58.00 ± 3.46%; 12.60 ± 1.34% respectively. Physical analysis of fried fish crackers showed decreasing in moisture content (from 4.41 – 5.40% to 2.76 – 3.75%), water activity (0.503 to 0.243 aw), L* and b* value (from 64 to 47 and 29 to 15), and hardness (1.773 to 0.793 kg), while an increase in a* value (0.71 to 5.78) and crispiness (6.94 to 12.45 kg/sec). The fried fish crackers with rice bran showed decreasing in moisture content (ranged from 3.24 – 3.87% to 1.96 – 2.69%), water activity (0.334 to 0.234 aw), L* value (from 62 to 51), hardness (2.065 to 1.090 kg) and crispiness (12.9 to 8.59 kg/sec), while increased in a* and b* value (from 3.98 to 9.28% and from 16.67 to 23.95% respectively). Physical analyses for fried fish crackers added with resistant starch showed an increase in moisture contents (from 2.75 – 3.47% to 4.08 – 4.54%), water activity (0.297 to 0.436aw), and a* and b* values (5.27 to 9.14%, and 21.09 to 25.27%, respectively), while a decrease in L* value (from 63 to 58%), hardness (from 2.110 to 1.117 kg) and crispiness (from 12.46 to 8.18 kg/sec) throughout 12 weeks of storage at all temperatures tested. The lipid yield for fried fish crackers was not stable within the storage time and the concentration of conjugated dienes and thiobarbituric acid reactive substances (TBARS) showed a gradual increase. The lipid yield of the fried fish crackers with rice bran and resistant starch increased within the storage time and the concentration of conjugated dienes and thiobarbituric acid reactive substances gradually decreased. The protein concentration of fried fish crackers and protein oxidation based on carbonyl content gradually increased. The protein concentration and protein oxidation of fried fish crackers with rice bran gradually increased. The protein concentration of fried fish crackers with resistant starch showed a gradual increase while a gradual decrease in protein oxidation. These results showed that fried fish crackers in this storage study had undergone lipid oxidation where there were signs of physical and chemical deterioration observed. In conclusion, it was noted that addition of 6% (w/w) rice bran flour and 16.7% (w/w) of resistant starch in fish crackers that stored at 25°C with suitable packaging materials has given a positive effect on the stability of the fried products.